Antimicrobial in vitro Study of Cosmos caudatus H.B.K Leaves Extract Towards Methicillin-Resistant Staphylococcus aureus (MRSA) - Febianti, Zahrah (Journal of Agromedicine and Medical Sciences, 2015)
Cosmos caudatus H.B.K leaves is known to have many active substances with antimicrobial effect such as saponin, flavonoid, poliphenol, volatile oil, costunolide, and 4,4â-bipyridin. This research is conducted to prove the antimicrobial effect of Cosmos caudatus leaves extract on gram positive Methicillin-Resistant Staphylococcus aureus (MRSA) in vitro. The sample of this research is served by Microbiology Laboratorium of Brawijaya University. An experimental study with tube dilution method was carried out. The treated groups are groups of bacteria treated with Cosmos caudatus leaves extract with a range concentrations of 14%; 12%; 10%; 8%; and 6%. The control group is groups treated with 0% extract. The result indicates that the MIC (Minimal Inhibitory Concentration) can not be observed due to the extractâs turbid green colour. The MBC (Minimal Bactericidal Concentration) is 14% for MRSA. Data analysis with CI=95% shows a significant difference of effects on the number of MRSA colonies growth (Anova, p = 0,000) with the change of extract concentrations. The correlation regression test shows a strong association between the extract concentration and the number of colonies growth (Correlation, r = -0,754, p=0,000). Cosmos caudatus leaves extract has antimicrobial effect on MRSA.Keywords : Cosmos caudatus leaves estract, Methicillin-Resistant Staphylococcus aureus (MRSA), antimicrobial.